The Effect of Using a Rocker Arm on the Performance and Efficiency of a 200cc 4 Stroke Motor - Afif Fakhruddin; A'rasy Fahruddin (Procedia of Engineering and Life Science, 2021)
In Indonesia, many people often use two-wheeled vehicles compared to four-wheeled vehicles, and so many people want the best speed and performance of their motorbikes compared to the manufacturer's standards. Modifying the camshaft or what is more familiarly known as "papas noken or camshaft" aims to increase volumetric efficiency and change the character of an engine, so that the engine produces more power and as needed. In racing motorbikes, modifications have been made to several systems and components, including the camshaft or camshaft to improve the motorbike's performance. Motor vehicle engine performance parameters include torque, power, mean effective pressure, specific fuel consumption, thermal efficiency, and air-material ratio. fuel air and fuel. In general, motorbikes for competition have been modified mechanical components and systems.